"Percepción de la imagen corporal y nivel de autoestima en la predicción del riesgo a trastornos de conducta alimentaria en mujeres adolescentes del Centro Educativo Particular "Nuestra Señora del Perpetuo Socorro". Trujillo - 2008" - Abanto Cueva, Katya Malena (2009)
The following co – relational descriptive kind research had as a main purpose to determine the prediction of the risk to eating disorders in adolescent of the Private Educational Center (PEC) “Nuestra Señora del Perpetuo Socorro”, and to establish the existing relation between Perception of Body Image and level of Self-esteem. The research had a sample of 132 adolescent’s women of the PEC. The gathered data was obtained through the application of three instrum ents: Self-esteem Inventories Stanley Coopersmith, Body Shape Questionnaire (BSQ) and Eating Attitude Test (EAT – 26). The data was admitted and processed in SPSS and the results were reported on Statistic s charts of simple and double entries. It is shown that 66.7 percent of the adolescents are satisfied with their body image; 50.8 percent have high self-esteem and 48.5 percent have half self-esteem; 86.4 percent present a low risk to eating disorders. Using the regression analysis, we conclude that a greater dissatisfaction with body image predicts a greater risk to eating disorders and has a significant statistic relation (p = 0.00 < 0.05), also a higher level of self-esteem predicts a lower risk to eating disorders and exist significant statistic relation (p = 0.00 < 0.05) among both variables.